Changes associated with lenalidomide treatment in the gene expression profiles of patients with del(5q) - Belickova, Monika; Cermak, Jaroslav; Dostalova Merkerova, Michaela; Veselá, Jitka; Krejcik, Zdenek; Cechova, Eliska; Zemanova, Zuzana; Michalova, Kyra; Votavova, Hana; Caniga, Miroslav; Neuwirtova, Radana; Jonasova, Anna (Clinical lymphoma, myeloma & leukemia, 2012)
UNLABELLED: We used microarray profiling to investigate the direct effects of lenalidomide on gene expression in isolated CD14(+) monocytes from 6 patients with del(5q). Our data demonstrate that changes in genes involved the tumor necrosis factor (TNF) signaling pathway and the bone marrow stroma, suggesting that treatment with lenalidomide may help restore the damaged niche and suppress the TNF signaling pathway. BACKGROUND: Lenalidomide is an effective treatment for patients with del(5q) and myelodysplastic syndrome (MDS) The exact mechanism of lenalidomide function and its impact on the prognosis of patients is not known exactly. MATERIALS AND METHODS: We used gene expression profiling to study the effect of lenalidomide therapy in peripheral blood CD14(+) monocytes of 6 patients with del(5q) and MDS. RESULTS: After lenalidomide treatment, genes involved in the tumor necrosis factor (TNF) signaling pathway that were upregulated in the patients before treatment decreased to the healthy control baseline expression level. This change in gene expression, in conjunction with increased expression of repressed genes that affect the stem cell niche (ie, CXCR4 and CRTAP), may exert a positive effect on treated patients. In contrast, we found that increased expression of the ARPC1B gene may have a negative impact on the stability of patient remission. CONCLUSION: The observed changes in gene expression described here may contribute to the identification of pathways that are affected by lenalidomide, which may help to explain the effects of this drug.
Keywords: chromozomální delece; Female; thalidomid; Thalidomide; Tumor Necrosis Factor-alpha; ženské pohlaví; Up-Regulation; lipopolysacharidové receptory; lidé; monocyty; protoonkogenní proteiny c-jun; upregulace; signální transdukce; studie případů a kontrol; Signal Transduction; prognóza; Lipopolysaccharide Receptors; Myelodysplastic Syndromes; myelodysplastické syndromy; TNF-alfa; Interleukin-1beta; Male; Monocytes; Case-Control Studies; Aged; Chromosome Deletion; Chromosomes, Human, Pair 5; nika kmenových buněk; Prognosis; komplex proteinů 2-3 souvisejících s aktinem; exprese genu; Actin-Related Protein 2-3 Complex; Proto-Oncogene Proteins c-jun; interleukin-1beta; lidé středního věku; transkriptom; senioři; mužské pohlaví; Transcriptome; Middle Aged; Stem Cell Niche; lidské chromozomy, pár 5; Gene Expression; Humans